Smell Phishy : A 2d Platform Game For Phishing Awareness - Ng, Man Teng (2023)
This project is discussing development of the Smell Phishy : 2d platform game for phishing awareness which can be played using a computer or laptop with keyboard and mouse. The problem statement of the project is that many methods to teach phishing awareness are inefficient. So, the 2D platform game can become an interesting way and can let players involve themselves inside the game. The 2D platform game can bring advantages which can have an interaction with the player. This can let players understand the importance of phishing awareness with fun and ease. The objective of this project is to study the technology behind the implementation of a 2D platform game, to design and develop a 2D platform game for phishing awareness, and to evaluate the functionality of the developed 2D platform game for the phishing awareness. The methodology selected is Rapid Application Development. The game was developed by using Unity and Visual Studio Code. There are 20 responses to the User Acceptance Test and most of them think the game is good but still need to improve.